Algal Autophagy Is Necessary for the Regulation of Carbon Metabolism Under Nutrient Deficiency - Kajikawa, Masataka; Fukuzawa, Hideya (Frontiers in Plant Science, 2020)
Autophagy is a recycling system for amino acids and other carbon- and nitrogen-containing cellular compounds. Although autophagy-related (ATG) genes required for autophagy are encoded by many algal genomes, their functional importance in microalgae under nutrient-deficient conditions has not been evaluated using autophagy-defective mutants. Recently, by characterizing an insertional mutant of the autophagy-related gene ATG8 that encodes a ubiquitin-like protein necessary for the formation of the autophagosome in the green alga Chlamydomonas reinhardtii, we have provided evidence that supports the following notions. ATG8 supports the degradation of triacylglycerol (TAG) and lipid droplets after the resupply of N to cells cultured in N-deficient conditions. ATG8 is also necessary for the accumulation of starch in phosphorus (P)-deficient conditions. Additionally, we showed that autophagy is not essential for maternal inheritance of organelle genomes in gametogenesis. In this review, we discuss the physiological roles of algal autophagy associated with nutrient deficiency revealed by the genetic and biochemical analyses using disruption mutants and reagents that inhibit the fatty acid biosynthesis and vacuolar H+-ATPase.